Diplomado de Recipientes a Presión (Inspección y Pruebas de Recipientes a Presión) - R.Rivera, Orlando (My University, 2005)
Objetivo General: Proporcionar los conocimientos mínimos requeridos para inspeccionar y probar cualquier recipiente sujeto a presión conforme a los requisitos obligatorios establecidos en la Sección VIII, División 1 del Código ASME.
Keywords: Recipientes a presión; Material inspections UG-93, UG-84(j) rejection, repairs of materials, material identification UG-77, material test report, UG-93, certificate of compliance, P numbers to watch, inspection of welds, radiography requirements section VIII division 1, table UCS-57, UW-51 full R.T., full radiography acceptance criteria, UW-52 spot R.T., spot radiography acceptance criteria, UHA-21 welded joints, ULT-57 examination, ultrasonic requirements section VIII division 1, ultrasonics, P.T. and M.T., UHA-34 liquid penetrant examination, required N.D.E. pressure testing, hydro test, minimum hydrostatic test pressure, combination units, cast iron vessels, inspection of the pneumatic test, test gauges UG-102, stamping directly on the vessel